Akhlaqul Banin as a Paradigm of Islamic Character Education: An Implementation Study at Madrasah Aliyah Negeri 2 Kuningan - Abdurrahman Atsa’lawi; Mukhlisin Mukhlisin (Indonesian Journal of Islamic Education and Learning, 2026)
Character education in Islamic educational institutions faces persistent challenges in bridging the gap between religious knowledge and its behavioral internalization among students. This study investigates Akhlaqul Banin a classical Islamic moral text by Umar bin Ahmad Baradja as a paradigm of Islamic character education and examines its implementation at Madrasah Aliyah Negeri (MAN) 2 Kuningan, West Java, Indonesia. The study aims to analyze the conceptual framework of Akhlaqul Banin, describe its pedagogical implementation, identify supporting and constraining factors, and evaluate its outcomes on students' character development. Employing a qualitative case study design with thematic analysis and conceptual framework reconstruction, data were collected through in-depth semi-structured interviews, participant observation, and document analysis involving 28 participants over three months. Findings reveal that Akhlaqul Banin constitutes a coherent three-pillared paradigm comprising al-adab al-ruhani, al-adab al-ijtima'i, and al-adab al-ilmi. Implementation through contextual discussion, bandongan, and behavioral habituation produced a mean character assessment gain score of +0.39 across seven Islamic character indicators. The study concludes that Akhlaqul Banin, when implemented through contextually responsive pedagogy within a supportive institutional environment, serves as an effective and theoretically robust paradigm for Islamic character education in contemporary madrasah settings.